Hamlet [videorecording (DVD)] - Zeffirelli, Franco; Gibson, Mel; Close, Glenn, 1947-; Bates, Alan, 1934-2003; Scofield, Paul, 1922-2008; Shakespeare, William, 1564-1616 (Warner Home Video, 2004)
Hamlet, a prince of medieval-era Denmark, senses treachery behind his royal father's death. His mother is all too dangerously entangled in that treachery. This film portrays Shakespeare's immortal tale of high adventure and evil deeds.